MODAL SOSIAL DALAM PENGELOLAAN ZAKAT PERSPEKTIF AL-QUR’AN: Analisis Trust, Jaringan, dan Norma Islam pada Lembaga Amil Zakat dan BAZNAS - Halwa Halimatusadiyah; Risa Aprilida; Dara Tsanya Abdul Rohim; Lina Marlina (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Zakāt is a crucial element in Islam due to its spiritual and socio-economic roles. This study aims to analyze the effectiveness of zakāt management at zakāt monitoring institutions (LAZ) and BAZNAS, focusing on social capital, particularly trust and networks, along with the role of Islamic principles. The research will involve examining academic articles, books, and official publications regarding zakāt and social capital, conducting literature reviews and document analyses. The findings reveal that trust is a major factor influencing the success of zakāt distribution and collection among transparent organizations. Furthermore, social networks that include institutions, local communities, and government bodies enhance the scope of zakāt distribution and promote the empowerment of muzakkī (donors). Islamic principles ensure that zakāt is managed effectively and ethically, in accordance with sharīa (Islamic law). As a result, enhanced trust, networks, and the application of Islamic principles strengthen the integrity of the zakāt system, increasing muzakkī engagement and effectively reducing social inequalities.